2009
DOI: 10.1371/journal.pone.0007244
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feedback Governs Gonadotrope Frequency-Decoding of Gonadotropin Releasing Hormone Pulse-Frequency

Abstract: The synthesis of the gonadotropin subunits is directed by pulsatile gonadotropin-releasing hormone (GnRH) from the hypothalamus, with the frequency of GnRH pulses governing the differential expression of the common α-subunit, luteinizing hormone β-subunit (LHβ) and follicle-stimulating hormone β-subunit (FSHβ). Three mitogen-activated protein kinases, (MAPKs), ERK1/2, JNK and p38, contribute uniquely and combinatorially to the expression of each of these subunit genes. In this study, using both experimental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 48 publications
(80 reference statements)
1
57
0
Order By: Relevance
“…Kanasaki et al initially observed that slow GnRH pulses triggered a more rapid and sustained phosphorylation of ERK1/2 than fast pulses (8). Subsequently, the feedback activity of MKP1, which inactivates MAPK via dephosphorylation, was found to modulate GnRH-induced ERK activation and gonadotropin response to GnRH (34,35). Finally, MKP1 expression was shown to be predominant under high GnRH frequency compared with low GnRH frequency (36).…”
Section: Discussionmentioning
confidence: 99%
“…Kanasaki et al initially observed that slow GnRH pulses triggered a more rapid and sustained phosphorylation of ERK1/2 than fast pulses (8). Subsequently, the feedback activity of MKP1, which inactivates MAPK via dephosphorylation, was found to modulate GnRH-induced ERK activation and gonadotropin response to GnRH (34,35). Finally, MKP1 expression was shown to be predominant under high GnRH frequency compared with low GnRH frequency (36).…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic oscillatory dynamics of the ERK pathway would affect the manner in which it would respond to stimuli from these various sources, especially if they displayed pulsatile or oscillatory behavior as well. For example, the ERK pathway has been shown to respond to pulsatile gonadotrophin-releasing hormone (GnRH) secretion and calcium oscillations and that negative feedback control through ERK is involved in frequency decoding [38,39 ]. It has also been shown through a theoretical analysis that multilevel cascades such as the ERK pathway can act as band-pass filters that respond optimally to calcium signals of a particular frequency [40,41].…”
Section: Implications Of Erk Oscillations On Cross-talk With Other Simentioning
confidence: 99%
“…GnRH-induced signaling to the gonadotropin genes is predominantly via the PKC pathway and downstream MAPK cascades, including extracellular signal-related kinase 1/2 (ERK1/ 2), Jun N-terminal kinase (JNK), p38 MAPK, and big MAPK (BMK or ERK5), while PKA is also activated following GnRH-induced increases in cyclic AMP (29,42). Many of the transcription factors that regulate expression of the gonado- tropin genes are activated through phosphorylation by these kinases and thus contain pSer/Thr-Pro motifs.…”
mentioning
confidence: 99%